Mesoscale and submesoscale turbulence in the Northwest Pacific Ocean revealed by numerical simulations. (December 2022) - Wang, Shihong; Song, Zhenya; Ma, Weidong; Shu, Qi; Qiao, Fangli
Abstract: As the intermit between geostrophic-balanced mesoscale eddies and three-dimensional dissipation, submesoscale turbulence (1–50 km) plays a key role in the ocean energy cascade. Based on the output of 1/48° MITgcm llc4320 simulation, mesoscale and submesoscale turbulence in the upper ocean and kinetic energy (KE) cascade between them are investigated in two different mesoscale dynamical regimes. When the timing of mesoscale seasonality varies with the mesoscale dynamical regimes, the timing of submesoscale seasonality is almost uniform. In this 1/48 o simulation, the inverse KE cascade, through which mesoscale KE is transferred from small scales to larger scales in altimeter observation, expands farther into the submesoscale range, with a minimum of about 15 km. The inversely transferred submesoscale KE is 1–2 orders of magnitude larger than that transferred forward. Both the inverse and forward KE cascades vary seasonally. While the amplitude of the forward KE cascade changes synchronously with the mixed layer depth, the amplitude of the inverse KE cascade lags behind them by ∼1-month This is due to nonlinear interactions between submesoscale processes and more slowly evolving mesoscale eddies which takes a little longer than direct dissipation. The inverse KE cascade leads to the mesoscale seasonality in the Kuroshio Extension, which is invisible in conventional altimeter observation. In terms of depth dependency, both the eddy kinetic energy (EKE) and normalized vertical vorticity ( ξ / f ) decrease rapidly with depth in the upper ocean, while the EKE-containing scale increases with depth and the ξ -containing scale has a large core in the mixed layer. It indicates that the upper ocean is full of mesoscale eddies on a relatively small scale which are accompanied by active submesoscale turbulence. The submesoscale seasonality is still significant at 300–400 m, and shows vertically consistency in the whole upper ocean, so there may be downward development in the nonlinear evolution of submesoscale turbulence. Highlights: The timing of mesoscale seasonality varies with the mesoscale dynamical regimes, while the submesoscale seasonality does not. The inversely transferred submesoscale KE is 1–2 orders of magnitude larger than the forwardly transferred in llc4320. The inverse KE cascade lags behind the forward KE cascade by ∼1-month. With the improving of the model simulation, the inverse KE cascade expands farther down to the submesoscales to 15 km. Both mesoscale and submesoscale turbulence show well vertically consistent seasonal variability in the upper ocean.